Preparation and Tests of MR Fluids With CI Particles Coated With MWNTs - Guo, Ying-Qing; Sun, Chun-Li; Xu, Zhao-Dong; Jing, Xingjian (Frontiers in Materials, 2018)
The magnetorheological (MR) fluid is a kind of smart material, whose shear yield stress can be adjusted through changing the strength of the external magnetic field, and this kind of changing only takes a few milliseconds. The MR fluid is composed of micro/nanometer ferromagnetic particles, carrier fluids and some additives. Among them, the performance of ferromagnetic particles will mainly affect the sedimentation stability and the magnetic saturation of the MR fluid. Therefore, they are expected to have characteristics of both low density and high magnetism. In this paper, the multi-walled carbon nanotubes (MWNTs) were adopted to coat on the carbonyl iron (CI) particles with grafting technology using ultrasonication and mechanical stirring. The coated CI particles with perfect core-shell structure were prepared and the influence of the dosages of grafting agent and MWNTs were tested. And then, MR fluids with CI particles coated with MWNTs were prepared and the coating effect was studied through surface topography analysis, particle density, and magnetic properties of composite magnetic particles and stability tests of the prepared MR fluids. The results showed that although the magnetic saturation of the prepared MR fluids with CI particles coated with MWNTs would reduce slightly, the particles density and the adsorption force between the particles were decreased effectively, which are both advantageous to the improvement of the sedimentation stability of MR fluids.